2018
DOI: 10.3390/ma11101963
|View full text |Cite
|
Sign up to set email alerts
|

Biofabrication of Electrospun Scaffolds for the Regeneration of Tendons and Ligaments

Abstract: Tendon and ligament tissue regeneration and replacement are complex since scaffolds need to guarantee an adequate hierarchical structured morphology, and non-linear mechanical properties. Moreover, to guide the cells’ proliferation and tissue re-growth, scaffolds must provide a fibrous texture mimicking the typical of the arrangement of the collagen in the extracellular matrix of these tissues. Among the different techniques to produce scaffolds, electrospinning is one of the most promising, thanks to its abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
127
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(134 citation statements)
references
References 189 publications
(313 reference statements)
7
127
0
Order By: Relevance
“…, and ). These results were in accordance with the previous studies on cell cultures carried out on PLLA/Coll electrospun bundles of aligned nanofibres (Sensini & Cristofolini, ; Sensini et al ., ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…, and ). These results were in accordance with the previous studies on cell cultures carried out on PLLA/Coll electrospun bundles of aligned nanofibres (Sensini & Cristofolini, ; Sensini et al ., ).…”
Section: Discussionsupporting
confidence: 93%
“…However, considering the different imaging investigations, the fibroblasts grown on the sheath of the hierarchical scaffolds showed an unprecedented phenomenon compared to previous cell studies (Hampson et al ., ; Alshomer et al ., ; Sensini & Cristofolini, ). In fact, the circumferential alignment and elongation of cells grown in the static condition was unexpected, even considering the slightly circumferential alignment of the sheath nanofibres (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a very recent study demonstrated that incorporating TMDs into electrospun nanofibers was a suitable approach for building biomimetic cellular scaffolds [10]. The final composite nanofibers showed some key characteristics of TMDs, such as a large surface area and good mechanical strength [8,11], while the fibrous features of the electrospun scaffold-which mimic the extracellular matrix-improved cellular adhesion and proliferation [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Among the most common synthetic biomaterials for tendon repair are electrospun PCL (poly‐ε‐caprolactone) and PLLA (poly‐ l ‐lactic acid) . Electrospinning can produce aligned fibrous scaffolds that promote cell alignment and their tensile moduli is higher than the natural biomaterials such as collagen and closer to that of a human tendon (around 1 GPa).…”
Section: Applications Of Advanced Biomaterials For Stem Cell Deliverymentioning
confidence: 99%